Epidemiological profile of stomach cancer mortality in the State of Piauí (Research, Society and Development, 2021)
The aim of this study was to characterize the epidemiological profile of mortality from gastric cancer in the state of Piauí from 2008 to 2018. This is an observational, descriptive and cross-sectional epidemiological study developed through the Mortality Information System. Data analysis was performed using simple descriptive statistics based on data provided by SIM. The occurrence of 1,491 deaths due to the studied neoplasm was verified. The capital Teresina also had the highest number of deaths (n=436). Of the individuals affected by gastric cancer and who died, it was observed that 62.24% were male. Information related to race/color suggested an extensive predominance of brown color with 63.98%. Regarding education, 32.46% of individuals had no education level. There was a high number of deaths from gastric cancer in individuals over 60 years old (70.42%). Regarding the place of occurrence of deaths, 57.20% of people died in hospitals. It is concluded that the profile of mortality from cancer studied in the state of Piauí follows, in many variables, a national trend. The findings of this research converge with the data present in the literature on the subject: gastric cancer remains a challenging pathology with fast progression, affecting mostly males and people aged 60 years or more. It is relevant to develop strategies to improve care and access to health services, with reduced waiting time for procedures, specialized exams and offering the best treatment for the stage of cancer and the patient's clinical conditions.